Consensus and contention in the food-versus-fuel debate - Rosegrant, Mark W.; Msangi, Siwa (Annual Reviews, 2014)
This review discusses research on linkages between biofuels, agriculture, and food security. The literature indicates that biofuel expansion affects land use, puts pressure on food and feed markets, and modestly reduces greenhouse gas emissions. Researchers readily identify these outcomes, as well as the multitude of factors besides biofuels that have driven up food prices in recent years. However, precision in quantifying the extent of the impacts and in attributing effects to various drivers is elusive, resulting in a wide range of estimates. Nevertheless, the central tendency is that a food-versus-fuel trade-off is created through biofuel production from food crops, and the continued expansion of biofuel production increases food commodity prices, reduces the availability of calories, and increases malnourishment in developing countries. Higher food prices particularly reduce the poor's access to food, which has possible long-term, irreversible consequences for health, productivity, and well-being.